Fatores que afetam a internacionalização de empresas familiares de produtos cosméticos - Vicente, Eliane (2021)
This paper analyzes how it occurs and what are the factors that affect the internationalization process of Brazilian family companies in the cosmetics industry. The study also assesses how the Behavioral Theories of internationalization (Uppsala model and Network Theory) corroborate this movement, seeking to understand the organizational structure of family businesses in this field and how human and financial resources are managed. It is assessed whether socio-emotional wealth, risk aversion and fear of loss of control impact on the internationalization process, investigating the mode of entry into the foreign market that these organizations practice and whether the presence of a non-family professional favors business management and the growth of the organization. A qualitative research of multiple cases was carried out with in-depth interviews, following a pre-established script containing explanatory questions. The study has the presence of three family-owned Brazilian companies in the cosmetics sector, focusing on hair treatment, which have already internationalized their products to several continents. The interviews were recorded, transcribed in full and with the aid of the NVivo software, the data were categorized. With the analysis of the data, it was possible to identify and conclude that family companies in the cosmetics industry begin the internationalization process using export as a means of entry, as it is a form that does not require as much knowledge and investment, compared to other modes. Companies search for regions where there is greater opportunity for their business, and from them, they choose the territories with the lowest psychic distance, thus facilitating their international expansion. It is recognized that having knowledge about the markets, their requirements, information about culture, language, and commercial practices, among other points, is extremely important for business success, and that learning does not cease, as the markets are dynamic and require constant updates from organizations. It appears that the relationship networks are relevant, both to recognize opportunities and to avoid complications in the development of the organization in the foreign market, and that getting involved in relationship networks reduces the time for the company to enter new territories, because they transfer knowledge, which is essential for operating in target markets. It is observed that socio-emotional wealth interferes in the way managers establish their decisions within the family business and that adopting conservative or liberal behavior will depend on the point of view they have on the business, on their management and handling characteristics, on the aim of control, power and omniscience of processes, personality and how flexible and willing they are in the face of the losses and gains that the management of a family business has. It was proven that generational transfer is an important factor for family businesses, that the next generations are better prepared and have a positive influence on the internationalization process. It is noted that investments in human resources contribute to both the development in the domestic and international markets and that the restriction of financial capital limits the company's progress.